(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
Metaphors certainly play a major role in revealing the artistic potential of the text. The study of language code and metaphorical sphere in linguistics is a requirement of the time. The article attempts to reveal their role in increasing the national-cultural specificity of the text